1970
DOI: 10.2172/4697914
|View full text |Cite
|
Sign up to set email alerts
|

Creep Behavior of Refractory Alloys in Ultrahigh Vacuum.

Abstract: SUMMARYSeveral Cb, Ta, Mo, and W base alloys have been creep tested with both constant and continuously increasing loads in a vacuum environment of < 1~1 0 -~ t o r r at temperatures and stresses chosen to provide between 1/2 and 1 percent creep i n times up to 20 000 hours. Isostatic design data a r e presented in the form of a.Larson-Miller plot for 1/2 o r 1 percent creep life for each of these refractory alloys. Elevated temperature tension test data from the tantalum base alloy T-111 showed a strain aging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1977
1977
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The large difference between the YS and UTS of the samples indicate a high level of work-hardening (which is also apparent in the stress-strain curves) and is consistent with the data from open literature. Sheffler et al [2] studied the strain aging behavior of T-111 and reported that the high strength (relative to pure Ta) may be caused by a complex atmosphere-dislocation interaction rather than by simple interstitial dislocation pinning. During aging, as the interstitial elements are redistributed and precipitated, the complex atmosphere-dislocation interactions weaken and the UTS drops.…”
Section: Tensile Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The large difference between the YS and UTS of the samples indicate a high level of work-hardening (which is also apparent in the stress-strain curves) and is consistent with the data from open literature. Sheffler et al [2] studied the strain aging behavior of T-111 and reported that the high strength (relative to pure Ta) may be caused by a complex atmosphere-dislocation interaction rather than by simple interstitial dislocation pinning. During aging, as the interstitial elements are redistributed and precipitated, the complex atmosphere-dislocation interactions weaken and the UTS drops.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…Of the possible Group V (V, Nb, Ta) and VI (Cr, Mo, W) refractory alloys, Ta-base T-111 (Ta + 8 wt% W + 2Hf) offers excellent formability and ductility at low temperatures, while showing good high temperature strength and alkali metal compatibility. Though tensile properties [1][2][3][4][5][6][7][8][9][10], creep testing [11][12][13][14], corrosion testing [15][16][17], and weldability studies [18][19][20] of T-111 have been investigated for different levels of cold work and annealing, bringing the technology to varying levels of maturity, the effects of aging on the mechanical properties is not as well understood. Earlier work on aging of T-111 under vacuum and liquid metal environments has shown conflicting results related to degradation in material ductility following exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic strain-aging has been observed previously in T-111 by Sheffler, Sawyer, and Steigerwald (ref. 8). Based on a comparison of the activation energy for strain aging and the activation energy for diffusion of each of the interstitial impurities in T-111, Sheffler, Sawyer, and Steigerwald concluded that oxygen is the critical interstitial specie responsible for dynamic strain aging i n T-111.…”
Section: Tensile Properties Of T a Alloysmentioning
confidence: 99%